The Use of Distance Fences In Reducing Dental Pain in The Community of the Bireuen District - Elfi Zahara (Science Midwifery, 2022)
Dental and oral health problems, especially dental cavities (caries), are still many complaints by both children and adults. Traditional medicine is still developing in the community by utilizing herbal plants. One of the plants that are widely used to reduce tooth pain is jatropha gum. Jatropha gum is still believed to reduce pain in teeth. This study aimed to determine the relationship between the use of jatropha sap in reducing tooth pain in the community in Cot Gapu Village, Juang City District, Bireuen Regency. This research is analytic with the cross-sectional approach. The population in this study were all people in Cot Gapu Village, Kota Juang District, Bireuen Regency, who suffered from toothache, totaling 82 people with a sample of 46 people. The Random Sampling technique did sampling. The study's results found a relationship between the use of Jatropha gum in reducing tooth pain in the community. Jatropha gum is used to cure dental caries by dripping one or two drops of sap into the tooth cavity. Jatropha sap contains flavonoids that can function as antifungal, antiseptic, and anti-inflammatory, also contains saponins that can stimulate collagen growth in the healing process and also have the effect of relieving pain and stimulating the formation of new cells.